Program Information and Application Procedures Fund for the Improvement of Postsecondary Education - Fund for the Improvement of Postsecondary Education (DHEW), Washington, DC.; Fund for the Improvement of Postsecondary Education (DHEW), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
The Fund for the Improvement of Postsecondary Education has as its main objective to improve postsecondary educational opportunities by providing assistance to educational institutions and agencies for a broad range of reforms and innovations. Grants and contracts may be awarded by the Fund for one of 8 purposes: (1) encouraging the reform, innovation, and improvement of postsecondary education, and providing equal educational opportunity for all; (2) the creation of institutions and programs involving new paths to career and professional training and new combinations of academic and experimental learning; (3) the establishment of institutions and programs based on the technology of communications; (4) the carrying out in postsecondary educational institutions of changes in internal structure and operations designed to clarify institutional priorities and purposes; (5) the design and introduction of cost-effective methods of instruction and operation; (6) the introduction of institutional reforms designed to expand individual opportunities for entering and reentering institutions and pursuing programs of study tailored to individual trends; (7) the introduction of reforms in graduate education, in the structure of academic professions, and in the recruitment and retention of faculties; and (8) the creation of new institutions and programs for examining and awarding credentials to individuals. (HS)
Educational level discussed: Higher Education.
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Finance; Educational Improvement; Educational Opportunities; Federal Aid; Grants; Higher Education; Postsecondary Education; Tuition Grants